2022
DOI: 10.1111/acel.13657
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and roles of RNA modifications in aging‐related diseases

Abstract: With the aging of the global population, accumulating interest is focused on manipulating the fundamental aging-related signaling pathways to delay the physiological aging process and eventually slow or prevent the appearance or severity of multiple aging-related diseases. Recently, emerging evidence has shown that RNA modifications, which were historically considered infrastructural features of cellular RNAs, are dynamically regulated across most of the RNA species in cells and thereby critically involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 192 publications
(187 reference statements)
0
13
0
Order By: Relevance
“…MicroRNA is a class of tiny noncoding RNAs with a length of about 18-25 nucleotides, which plays an important role in gene modifications at the transcriptional level (Ko et al, 2020). Studies have indicated that microRNA is associated with many age-related neurodegenerative diseases, including AD and amyotrophic lateral sclerosis (Jiapaer et al, 2022). Moreover, microRNA is also related to the ageing process of NSCs.…”
Section: Nscs Inhibit Ageing Through Regulation Of Micrornamentioning
confidence: 99%
“…MicroRNA is a class of tiny noncoding RNAs with a length of about 18-25 nucleotides, which plays an important role in gene modifications at the transcriptional level (Ko et al, 2020). Studies have indicated that microRNA is associated with many age-related neurodegenerative diseases, including AD and amyotrophic lateral sclerosis (Jiapaer et al, 2022). Moreover, microRNA is also related to the ageing process of NSCs.…”
Section: Nscs Inhibit Ageing Through Regulation Of Micrornamentioning
confidence: 99%
“…32 Key RNA modifications pertinent to PDs include N 6 -methylation of adenosine (m 6 A), N 1 -methylation of adenosine (m 1 A), 5-methylcytosine (m 5 C), pseudouridine (5-ribosyl uracil, Ψ), 7-methylguanosine (m 7 G), and adenosine to inosine (A-to-I) editing (Figure 2A). 33 By categorizing RNA and applying distinct treatments, modifications influence its trajectory in processes such as cellular differentiation, embryonic development, and responses to stress. Provided below is a summary of notable RNA modifications and their regulatory components associated with PDs (Table 1).…”
Section: Rna Modification Pathways and Enzymesmentioning
confidence: 99%
“…The common RNA modifications include N 6 methylation of adenosine (m 6 A), N 1 methylation of adenosine (m 1 A), N 7 -methylguanosine (m 7 G), 5-methylcytosine (m 5 C), 2′O-methylation (2′-O-Me or Nm), pseudouridine (5-ribosyl uracil or Ψ) and adenosine to inosine RNA editing (A-to-I editing), etc. ( Figure 1 ) [ 39 ]. Among these RNA modifications, m 6 A is the most abundant form in eukaryotic cells, extensively studied in recent years.…”
Section: Rna Epigenetics Mechanismsmentioning
confidence: 99%